22q11.2 DS syndrome as a genetic subtype of schizophrenia (2015)
Introduction The 22q11.2 deletion syndrome (22q11.2 DS) is associated with the microdeletion of this chromosomal region, and represents the second most common genetic syndrome after Down's syndrome. In patients with schizophrenia, 22q11.2 DS has a prevalence of 2%, and in selected groups can be increased to between 32-53%. Objective To describe the generalities of 22q11.2 DS syndrome as a genetic subtype of schizophrenia, its clinical characteristics, molecular genetic aspects, and frequency in different populations. Methods A review was performed from 1967 to 2013 in scientific databases, compiling articles about 22q11.2 DS syndrome and its association with schizophrenia. Results The 22q11.2 DS syndrome has a variable phenotype associated with other genetic syndromes, birth defects in many tissues and organs, and a high rate of psychiatric disorders, particularly schizophrenia. Likewise, it has been identified in clinical populations with schizophrenia selected by the presence of common syndromic characteristics. FISH, qPCR and MLPA techniques, and recently, aCGH and NGS technologies, are being used to diagnose this microdeletion. Conclusions It is important in clinical practice to remember that people suffering the 22q11.2 DS have a high genetic risk for developing schizophrenia, and it is considered that the simultaneous presence of this disease and 22q11.2 DS represents a genetic subtype of schizophrenia. There are clear phenotypic criteria, molecular and cytogenetic methods to diagnose this group of patients, and to optimize a multidisciplinary approach in their monitoring. © 2014 Asociación Colombiana de Psiquiatría.